Performance Analysis of Photovoltaic Induction Motor Drive for Agriculture Purpose - Neethu Raj P R; Vasanthi V (Institute of Advanced Engineering and Science, 2016)
This paper presents water pumping system using renewable source (solar) without the use of chemical storage batteries. In this converter-inverter circuit is used to drive Induction motor. The Converter used here is Two Inductor boost converter (TIBC), which consists of a resonant tank, voltage doubler rectifier and a snubber circuit. TIBC is designed to drive the three phase induction motor from PV energy. TIBC converter is also known as current fed multi resonant converter having high voltage gain and low input current ripple. Converter switches are controlled through hysteresis controller and ZCS resonant topologies. Solar PV power fluctuates according to irradiation level of sunlight and hence tracking of maximum power at all time is mandatory. SPWM control with third harmonic injection is used to trigger the IGBT’s in the inverter. The development is oriented to achieve a more efficient, reliable, maintenance free and cheaper solution than the standard ones, that uses DC motors or low voltage synchronous motors. The proposed method is verified with MATLAB/SIMULINK and the system simulation confirms the performance of the proposed system.